The broken window : a Lincoln Rhyme novel - Deaver, Jeffery (New York : Simon & Schuster, 2008)
The mysterious 522 commits vicious crimes and then plants ironclad evidence to implicate innocent men. This timely thriller reunites Lincoln Rhyme with his partner and paramour Amelia Sachs, as they face their toughest adversary yet
Keywords: Rhyme, Lincoln (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Serial murderers -- Fiction; Manhattan (New York, N.Y.) -- Fiction